Análise de desempenho de uma rede local sem fio para aplicações multimídia - Sergio Augusto Coelho Bezerra (2001)
This work presents a methodology that supplies subsidies in order to evaluate the acting of multimedia applications in Wireless Local Area Network. To understand the context of the work first we described some theoretical fundamentals on Wireless Local Area Network (WLAN) and Multimedia Applications. In what it concerns the Wireless Local Area Network, standardized as 802.11, we presented basic concepts on WLANs, taking the reader to know the patterns and components of these types of networks, as well as, their advantages and disadvantages, security, protocols, transmission technologies and their architectures. As the Multimedia Applications, we concentrated efforts to describe its concept and operation so the reader could understand the model of the traffic that would influence in the performance of the network. The multimedia applications worked in this research were the telnet, ftp, http, audio and video. As main earnings of this work we presented a methodology to simulate and to evaluate the performance of multimedia applications in WLAN, considering the Quality of Service (QoS) for heterogeneous traffics originating from of these applications. To show the application of the methodology we accomplished a case of study where we teach step by step how to use it. Besides, the tool of simulation used was the ns (Network Simulator), given its great using and acceptance in the academic universe.